Optimization of Tetrigona apicalis Propolis Extract using Glycerol Solvent with Shaking Ultrasound Assisted Extraction Method - Dwi Desmiyeni Putri; Syahdilla Anggiva Akhni Rarasati; Oktaf Rina; Isnina Isnina (Postgraduate, University of Mataram, 2025)
Tetrigona apicalis were known as lebah penyengat and its can be produce propolis were extracted by metode shaking ultrasound-assisted extraction (SUAE), which produces perfect extraction, higher yield and active content, and a shorter time. The purpose of this research were fined the optimum conditions for extracted its by using the SUAE method in glycerol solvent. It were done to raw propolis with size reduced, then solvent was added and macerated using shaker. It was processed with a sonicator, than filtered. The solvent used 70% glycerol, and the results of the propolis extract are processed using Response Surface Methodology (RSM). The optimal conditions of its process from the yield response shown were a stirring time of 28.76 minutes and an ultrasonic process time of 23.94 minutes with a yield of 4.238%. Based on statistical analysis using Minitab Version 19 software, stirring time and ultrasonic processing time are factors that have a significant influence on the yield of propolis extract produced. The model used is a quadratic model with R2 0.9191. A quadratic equation model was obtained which states the relationship between propolis extract yield and the varied factors X = 0.865 + 0.0091A – 0.0186B – 0.000006A2 + 0.00370.B2 + 0.00215AB